ECOLOGICAL ANALYSIS OF LIVING BENTHIC FORAMINIFERA IN SURFACE SEDIMENTS FROM THE SOUTH YATSUSHIRO KAI (SEA), SOUTHWEST KYUSHU, JAPAN - Rifardi , (JOURNAL OF COASTAL DEVELOPMENT, 2002)
Bottom sediments were collected from 74 stations in the South Yatsushiro Kai (Sea), Japan using gravity corer in March 1996. Aimed at clarifying the relation between living benthic foraminiferal assemblage and environmental conditions, the Q-mode cluster analysis was carried out based on the predominant species of living benthic foraminifera recognized at the topmost one centimeter of 73 core samples. The results of this study show a trend of a large number of living benthic foraminifera is found in central part of the sea, on the other hand, a small number is seen in the northern and southern part. The study area is characterized by 469 species of living benthic foraminifera belonging to 114 genera. In relation to the five divisions of the marine environment based on oceanographic data, mechanical analysis data and sedimentation rates, the foraminiferal assemblages in the South Yatsushiro Kai were grouped into five populations. Population I occupies the areas near the straits under the influence of strong tidal and bottom currents. Population II occupies the areas surrounding the straits (Gannoshiri Seto and Kurono Seto) influenced by water masses flowing through the straits. Population III occupies the areas of rather stagnant water masses in the northern and southern parts of the sea. Population IV occupies the areas located in the northeastern and southeastern parts of the sea, and influenced by river waters. Population V occupies the nearshore area located in the northeastern, and influenced by the water masses which flow southward from the North Yatsushiro Kai.